LAW OF CONTRADIKTION - Otajonov Gаyratjon Umarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article reveals the meaning and essence of the law of contradiction - one of the general laws of logical thinking, classifies the manifestations of logical contradiction, and also emphasizes the importance of the law of contradiction in the process of logical thinking.